A Sephardi Sea: Jewish memories across the modern Mediterranean - Miccoli, Dario (Sephardi and Mizrahi Studies, 2022)
A Sephardi Sea explores how practices of memory- and heritage-making has filled an identity vacuum in the three countries and helps the Jews from North Africa and Egypt to define their Jewishness in Europe and Israel today.